(untitled) (Medico Legal Update, 2020)
The study was conducted in the city of Kirkuk in the period from October 2019 to March 2020, which included 100 pregnant women with type 2 diabetes who attended obstetric, gynaecology and paediatric hospital in Kirkuk city and 100 people intact and without any chronic disease .. The study included the laboratory examination of the reactions samples, where close quantities of midstream urine were collected for both groups. After collecting the calories, the calories were examined microscopically, and then the reactions were transplanted into the available culture media to isolate the aetiology of urinary tract infections such as blood agar and MacConkey agar, and the CLED agar to isolate and diagnose bacteria of all kinds .. In addition, the sensitivity test for antibiotics was applied by the feeding medium where the method were relied upon Global standard bacteriological culture procedure, isolation and diagnosis by biochemical tests. Among diabetes mellitus patients included in this study, 80 % were positive for UTI patients, while 20 % were negative for UTI. According to the distribution of the isolated bacteria among the study groups, the common isolated bacteria among DM was E .coli which constituted 26.36% followed by K. pneumoniae which constituted 17.27%, S. aureus and P. mirabilis which constituted 8.18% and the lowest percentage was Enterobacter cloacae for 1.81%. In this study S. aureus showed high rate of sensitivity to ciprofloxacin and oxacillin (88.23%) while it was resistant to ampicillin and lincomycin with rate of 100%. Staphylococcus epidermidis showed high rate of sensitivity to tobramycin and oxacillin (92.85%) while it was resistant to ampicillin, lincomycin and amoxicillin (100%) Escherichia coli showed high rate of sensitivity (93.02%) to ceftazidim and it was 100% resistant to oxacillin and lincomycin. Klebsiella pneumoniae showed high rate of sensitivity (81.48 %) to amoxiclave and it was resistant to ampicillin, tetracycline, erythromycin, oxacillin and lincomycin (100%).